TECHNOLOGICAL FEATURES OF PRODUCTIVITY FORMATION AND QUALITY IMPROVEMENT OF MEADOW CLOVER GREEN BIOMASS - Dudar , І.; Shuvar , І.; Korpita , Г.; Pavkovych , С.; Tkachuk , В.; Ratskyi , М. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The article emphasizes the technological aspects of enhancing productivity and improving the quality of meadow (also called red) clover (Trifolium pratense L.) green mass in contemporary agriculture. It explores scientific methods for assessing the effects of soil tillage and fertilization techniques on both the yield and qualitative characteristics of meadow clover green mass. The provision of high-quality feed for livestock remains a top priority for agricultural science and practice. The article outlines strategies to optimize energy resources through the establishment of high-yielding agrophytocenoses of perennial leguminous grasses, specifically red clover, which is well-suited for the conditions of the Western Forest-Steppe of Ukraine due to its high protein content. The study presents findings on the variability of qualitative indicators of red clover green mass based on different tillage and fertilization methods, conducted during 2023–2024. Three primary tillage methods were evaluated: conventional (control), chisel, and tiered (layered), with a particular focus on the beneficial impact of the PYa-4-40 plow at a depth of 14–16 cm, under two types of fertilization systems (organic and organic-mineral). The research indicated that the method of primary tillage and the fertilization system applied to dark gray podzolic light loam soil did not significantly impact the qualitative indicators of green mass yield for the Truskavchanka red clover variety. Plowing with the PYa-4-40 plow resulted in a modest increase in the nutritional value of the green mass when compared to conventional and chisel tillage methods. The benefits of tiered plowing include enhanced water, air, and nutrient conditions, which create optimal circumstances for producing high-quality feed. Furthermore, the integration of tiered tillage with organic-mineral fertilization yielded the highest levels of dry matter content (18.23%), digestible protein yield (12.80 c/ha), and concentrations of key macroelements (nitrogen – 2.73%, phosphorus – 0.37%, potassium – 2.13%).